2019
DOI: 10.1029/2018wr023113
|View full text |Cite
|
Sign up to set email alerts
|

A Whittaker Biome‐Based Framework to Account for the Impact of Climate Change on Catchment Behavior

Abstract: Rainfall-runoff models are often used to simulate the impact of long-term climate change on future water availability. A common assumption in most modeling frameworks is that catchment's hydrologically relevant characteristics, represented via model parameters, remain constant. However, several studies present evidence on the contrary and suggest potential biases in estimates of future streamflow due to this assumption. Regardless, there is a lack of modeling frameworks that account for the possible impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…1a, b). We projected MAT and MAP at sampling sites in a Whittaker biome plot to show how plant biomes are distributed in association with long-term precipitation and temperature [25]. We collected climate data with a high temporal and spatial resolution from 2007 to 2013.…”
Section: Introductionmentioning
confidence: 99%
“…1a, b). We projected MAT and MAP at sampling sites in a Whittaker biome plot to show how plant biomes are distributed in association with long-term precipitation and temperature [25]. We collected climate data with a high temporal and spatial resolution from 2007 to 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Significant evidence has emerged to suggest that many conceptual hydrologic models calibrated on dry (wet) periods show biases when used for projecting hydrology in wet (dry) periods (Coron et al, 2014; Dakhlaoui et al, 2017; Fowler et al, 2016; Li et al, 2012; Merz et al, 2011; Saft et al, 2016; Vaze et al, 2010). Therefore, frameworks of changing parameters were developed under different climate change scenarios (Deshmukh & Singh, 2019; Bai et al, 2021). Alternatively, modelling studies of physics‐based models have shown the important role of groundwater in catchment processes (Condon, Atchley, & Maxwell, 2020; Condon, Markovich, et al, 2020; Soulsby et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Our approach begins by applying a 12-parameter rainfall-runoff model over each watershed 's historical (1980-1990) climate to obtain behavioral parameter sets (Section 2.1). Following Deshmukh and Singh (2019), we update all behavioral parameter sets for each watershed that undergoes a climate-induced biome transition. The updated sets are used to simulate runoff in the postchange analysis period of 1999-2009.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Deshmukh and Singh (2019) proposed a TSFT approach based on the Whittaker‐biome plot (Whittaker, 1970). This plot is based on the biological concept of convergence—similar environmental conditions lead to the evolution of adaptations that result in resemblance between unrelated organisms (Ricklefs, 2008).…”
Section: Introductionmentioning
confidence: 99%